Analisis Perencanaan Bendung (Studi Kasus Bendung Botung) - Sadewa Sabihi; Manyuk Fauzi; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research will discuss the analysis of the stability of the dam in the area Botung against weir botung in the area Botung it self actually has no weir bronjong but the dam is temporary and has damaged it needs to be made weir remains to be utilized in the long term, so it takes the design of the lighthouse and the pool megrim secure against rolling, sliding and piping. Based on the results of the discussion of final project study entitled